Upaya Meningkatkan Output Belajar Peserta Didik Dalam Mata Pelajaran Ekonomi Dengan Penerapan Model Problem Based Learning (PBL) - Rizkinara, Faradisa; Kurniawan, Riza Yonisa; Basir, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The purpose of the research is to increase the result of economic learning of students in class XI IPS 2 at SMAN 1 Ngoro by the application of the Problem Based Learning model. The research subjects were students of class XI IPS 2 at SMAN 1 Ngoro. This research was conducted in two cycles. Before the activities of cycles I and II, pre-action learning was carried out. Research cycles I and II were both carried out in two meetings. Data collection using student worksheets, observation sheets and tests. Based on the results of data analysis, the result of learning of economic students on APBN and APBD materials showed that there was an increase of 5.56% from cycle I to cycle II. So it can be concluded that the result of economic learning of class XI IPS 2 SMAN 1 Ngoro by the Problem Based Learning (PBL) learning model have increased.